PERBEDAAN MORALITAS SISWA DENGAN MODEL PORTOFOLIO DAN CTL - Asnur Vevy; Eddy Purnomo; Yon Rizal (FKIP Unila, 2014)
The method which used in this research is comparative study with experimental approaches. Hypotheses of test using anava and the t-test two independent samples.Based on the analysis of data it obtained the following research findings, 1) there is a difference of student morality in learning of IPS between students who are using portofolio and CTL. 2) there are difference of morality in the learning of IPS between students who have intrapersonal with interpersonal intelligence. 3) There is no interaction between learning model with intelligence 4) students morality in learning of IPS which is using portofolio is higher than CTL on students who have intrapersonal intelligence. 5) students morality in learning of IPS which is using portofolio is higher than CTL on students who have interpersonal intelligence 6)students morality in learning of IPS which have the intrapersonal intelligence is lower than the interpersonal intelligence in portofolio. 7) students morality in learning of IPS which have the intrapersonal is lower than the interpersonal by using CTL.Metode dalam penelitian ini studi banding dengan pendekatan eksperimen. Tes Hipotesis menggunakan anava dan t-test dua sampel independen. Berdasarkan analisis data diperoleh 1) Terdapat perbedaan moralitas siswa dalam pembelajaran IPS menggunakan portofolio dan CTL. 2) Terdapat perbedaan moralitas dalam pembelajaran IPS yang berkecerdasan intrapersonal dan interpersonal. 3) Tidak ada interaksi model pembelajaran dengan kecerdasan. 4) Moralitas siswa dalam pembelajaran IPS dengan portofolio lebih tinggi dibandingkan CTL pada siswa berkecerdasan intrapersonal. 5) Moralitas siswa dalam pembelajaran IPS menggunakan portofolio lebih tinggi dibandingkan CTL pada siswa berkecerdasan interpersonal. 6) Moralitas siswa dalam pembelajaran IPS yang berkecerdasan intrapersonal lebih rendah dibandingkan interpersonal menggunakan portofolio. 7) Moralitas siswa dalam pembelajaran IPS yang berkecerdasan intrapersonal lebih rendah dibandingkan interpersonal menggunakan CTL.Kata kunci: ctl, intrapersonal, interpersonal, moralitas, portofolio